2022
DOI: 10.1021/acs.energyfuels.2c00964
|View full text |Cite
|
Sign up to set email alerts
|

Mini-review on Recent Advances in the Application of Surface-Active Ionic Liquids: Petroleum Industry Perspective

Abstract: Ionic liquids have emerged as a promising new material for a wide range of industrial applications, because of their unique structures and properties. Ionic liquids possess exceptional properties such as chemical and thermal stability, negligible vapor pressure, or solvency power for different types of molecules. Ionic liquids find their application in different operations in petroleum industry. The purpose of this paper is to review previously published works on the application of the IL in various areas of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 131 publications
0
18
0
Order By: Relevance
“…Microbial toxicity screening results indicated that none of the tested compounds would be expected to show inhibition towards microbes in inoculum during CBT. Thus, based on results from antimicrobial activity testing all six IL parent compounds (1)(2)(3)(4)(5)(6) and their PTPs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were given equal priorities for further studies and were tested for their aerobic biodegradability. Biodegradation testing was performed using modified CBT method and each test ran for up to 33-42 days.…”
Section: Aerobic Biodegradation Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Microbial toxicity screening results indicated that none of the tested compounds would be expected to show inhibition towards microbes in inoculum during CBT. Thus, based on results from antimicrobial activity testing all six IL parent compounds (1)(2)(3)(4)(5)(6) and their PTPs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were given equal priorities for further studies and were tested for their aerobic biodegradability. Biodegradation testing was performed using modified CBT method and each test ran for up to 33-42 days.…”
Section: Aerobic Biodegradation Testingmentioning
confidence: 99%
“…For specific proposed breakdown pathways for 1-6, see ESI-1. Biodegradation graphs for amino acid ILs (1 and 2) and their PTPs (7-13) and dipeptide ILs (3)(4)(5)(6) and their PTPs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) are shown on Figs. 2 and 3.…”
Section: Aerobic Biodegradation Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 More so, the world energy supply is being continually dominated by liquid hydrocarbon oil and gas resources. 48 Accordingly, as seen in Figure 2, unconventional resources including tight oil, natural gas liquids, and heavy/extra-heavy oil (bitumen) constitute significant contributors in the liquid fuel supply chain in the present and projected periods. 83 Heavy oil including bitumen represents a huge hydrocarbon energy resource with over six trillion barrels deposited in several places around the world.…”
Section: Introductionmentioning
confidence: 99%